PENGARUH PEMBELAJARAN BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA NEGERI 12 MAKASSAR - Mindar, Putra; Syahid, Akhmad; Nengsih, Ratika; Mustamin; Wahab, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of Information and Communication Technology (ICT)-based learning on students' learning outcomes in the Islamic Religious Education subject at SMA Negeri 12 Makassar. The type of research used is quantitative with an ex-post-facto approach. The population consisted of all eleventh-grade students at SMA Negeri 12 Makassar, while the sample comprised 190 students selected using the proportionate stratified random sampling technique. Data were collected through questionnaires to measure ICT-based learning, which included the components of hardware, multimedia, and online learning platforms, as well as students' report card scores to measure learning outcomes. The data were analyzed using descriptive statistics, classical assumption tests, and multiple linear regression analysis. The results indicate that, partially, the variables of hardware, multimedia, and online learning platforms have a positive and significant effect on students' learning outcomes. Simultaneously, these three variables also have a significant effect on students' learning outcomes, with an Adjusted R² value of 0.5413, indicating that 54.13% of the variance in students' learning outcomes can be explained by ICT-based learning, while the remaining 45.87% is influenced by other factors outside the research model. The study concludes that ICT-based learning has a positive and significant effect on students' learning outcomes in the Islamic Religious Education subject at SMA Negeri 12 Makassar.